Tending the sick: Observations of epimeletic behavior in humpback whales towards conspecifics during entanglement events - Rachel Cartwright; Ed Lyman; Amy Venema; Jens J. Currie; Stephanie H. Stack; Adam A. Pack; Lars Bejder; Martin Van Aswegen; Sadie K. Wright; Dorothy Horn (PLoS ONE, 2025)
Anthropogenic impacts on marine systems are increasing in frequency, geographic range and severity. While changes in climate will likely lead to the greatest impacts at the system-level, for marine megafauna, entanglement in marine debris also constitutes a pernicious threat. For baleen whales, in regions where high productivity and prolific fisheries overlap, entanglement is emerging as a component of their life history: In some of these regions, entanglement comprises the leading cause of serious injury and mortality. Additionally, up to 80% of whales carry scars indicative of entanglement, and associated declines in long-term health are reducing fecundity. Here, we describe behavioral traits seen in humpback whales during entanglement incidents. Specifically, we focus on reports of humpback whales that have remained in association with entangled whales during these incidents and apply the term “companion whales” in reference to these whales. Reports reviewed include a detailed account of a recent incident observed in Hawaiian waters, a compilation of 62 accounts of similar behavior extracted from 414 reports of entanglement events provided by regional entanglement response networks, and a series of six reports associated with whaling activities. The similarities between the current behavior of companion whales and behaviors observed during whaling activities suggest that this may be an example of behavioral plasticity, underscoring the expanding behavioral repertoire exhibited by baleen whales, and highlighting their potential resilience as they respond to the changing marine environment.